Influence of relational-oriented exchange on outsourcing success in supplier-manufacturer relationships: A financial performance perspective - Hassan, Mohamad Ghozali; Othman, Abdul Aziz; Ismail, Mohd Azril (Engineering and Technology Publishing, 2016)
The role of relational-oriented exchange is an important concern of competitiveness sustainability in developing an outsourcing company. Analyzing the influence of relational-oriented exchange on the financial performance of outsourcing success enables greater business value over time.This paper aims to study the relational-oriented exchange in terms of structural and process dimensions improving the outsourcing performance among manufacturing industries.An empirical study was applying partial least square and structural equation modelling using responses from a sample list of all electric and electronic manufacturing industries in Malaysia.This is done with the help of a statistical tool, SmartPLS as a new quantitative research demonstrated to support the positive relationship between relational-oriented exchange and outsourcing success from a financial performance perspective.